Comparison of Nasal Colonization of Methicillin-Resistant Staphylococcus aureus in HIV-Infected and Non-HIV Patients Attending the National Public Health Laboratory of Central Nepal - Kalash Neupane; Binod Rayamajhee; Jyoti Acharya; Nisha Rijal; Dipendra Shrestha; Binod G C; Mahesh Raj Pant; Pradeep Kumar Shah (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Staphylococcus aureus is a cardinal source of community- and hospital-acquired infection. HIV infection is a well-recognized risk factor for methicillin-resistant S. aureus (MRSA) carriage and infection. Intrinsically developed antibiotic resistance has sharply increased the burden of MRSA which is often associated with morbidity and mortality of the patients. Moreover, nasal carriage of S. aureus plays a significant role in spread of community-associated (CA) S. aureus infections. Methods. This study was conducted from June 2016 to December 2016 at National Public Health Laboratory (NPHL), Kathmandu, with an aim to assess the rate of S. aureus nasal carriage and MRSA carriage among HIV-infected and non-HIV patients. A total of 600 nonrepeated nasal swabs were analyzed following standard microbiological procedures, where 300 swabs were from HIV-infected patients while remaining 300 were from non-HIV patients. The isolates were identified on the basis of colony characteristics and a series of biochemical tests. The antibiotic susceptibility test (AST) was performed by the modified Kirby–Bauer disc diffusion method. Inducible clindamycin resistance in isolates was confirmed by the D-test method. Results. Overall, out of 600 nasal swabs of patients tested, 125 (20.8%) were S. aureus nasal carriers which included 80 out of 300 (26.66%) among HIV-infected patients and 45 (15%) out of 300 among non-HIV patients, and the result was statistically significant (p=0.0043). Among the isolated S. aureus, 11 (13.8%) MRSA were confirmed in HIV-infected while 3 (6.7%) MRSA were detected from non-HIV patients. A higher number of S. aureus carriers was detected among HIV-infected males 40 (26.49%), whereas MRSA carriage was more prevalent among HIV-infected females 7 (5.1%). Among the HIV-infected, patients of age group 31–40 years were the ones with highest carriage rate 36 (45%), while in non-HIV patients, the highest rate 13 (28.9%) of carriage was detected among the patients of age group 21–30 years. Statistically significant difference was found between S. aureus carriage and HIV infection in patients (p<0.05). Higher rate 2/3 (66.7%) of inducible clindamycin resistance in MRSA was detected from non-HIV patients in comparison to HIV-infected patients 7/11 (63.63%) while the result was statistically insignificant (p>0.05). All the MRSA isolates (100%) were resistant against co-trimoxazole while ciprofloxacin showed high rate of sensitivity towards both MSSA and MRSA. None of the isolates were detected as VRSA. The major factors associated with nasal colonization of S. aureus were close personal contact, current smoking habit, and working or living in a farm (p<0.05). Conclusion. Regular surveillance and monitoring of MRSA nasal carriage and antibiotic susceptibility pattern are of prime importance in controlling S. aureus infections especially in high risk groups like HIV-infected patients.